A simple colorimetric assay for specific detection of glutathione-S transferase activity associated with DDT resistance in mosquitoes. - Evangelia Morou; Andrew J Dowd; Shavanti Rajatileka; Andrew Steven; Janet Hemingway; Hilary Ranson; Mark Paine; John Vontas (Public Library of Science (PLoS), 2010)
BACKGROUND: Insecticide-based methods represent the most effective means of blocking the transmission of vector borne diseases. However, insecticide resistance poses a serious threat and there is a need for tools, such as diagnostic tests for resistance detection, that will improve the sustainability of control interventions. The development of such tools for metabolism-based resistance in mosquito vectors lags behind those for target site resistance mutations. METHODOLOGY/PRINCIPAL FINDINGS: We have developed and validated a simple colorimetric assay for the detection of Epsilon class Glutathione transferases (GST)-based DDT resistance in mosquito species, such as Aedes aegypti, the major vector of dengue and yellow fever worldwide. The colorimetric assay is based on the specific alkyl transferase activity of Epsilon GSTs for the haloalkene substrate iodoethane, which produces a dark blue colour highly correlated with AaGSTE2-2-overexpression in individual mosquitoes. The colour can be measured visually and spectrophotometrically. CONCLUSIONS/SIGNIFICANCE: The novel assay is substantially more sensitive compared to the gold standard CDNB assay and allows the discrimination of moderate resistance phenotypes. We anticipate that it will have direct application in routine vector monitoring as a resistance indicator and possibly an important impact on disease vector control.